Clinical outcomes of post-surgery osteoporosis treatment in elderly intertrochanteric fracture patients: a prospective study - Siwach, Ishaan; Krishna, Loveneesh G.; Talwar, Jatin; Rustagi, Ashish; Keer, Navdeep S. (International Journal of Research in Orthopaedics, 2024)
Background: This study aims to evaluate the clinical and functional outcomes of administering zoledronic acid in elderly patients undergoing surgical management of hip fractures. The goal is to assess the impact on mortality, postoperative complications, and functional recovery as measured by the modified Harris hip score. Methods: A prospective study was conducted over 18 months at a tertiary care center in New Delhi, India, involving 42 patients aged 60 and above with intertrochanteric femur fractures. Patients received surgical fixation and standard postoperative care. Zoledronic acid (5 mg) was administered intravenously three months post-surgery. Data on demographics, injury-to-surgery interval, fracture type, DEXA score, and functional outcomes were collected at follow-ups of 6 weeks, 3 months, 6 months, and 12 months. Results: The mean age of participants was 72.67 years. Zoledronic acid administration was associated with a 9.5% mortality rate. Functional outcomes, measured by the modified Harris hip score, significantly improved from a mean of 42.14 at 6 weeks to 77.68 at 12 months (p<0.001). Younger patients (<70 years) had significantly better scores at 3 months compared to older patients (>80 years). However, no significant differences were observed at 6 and 12 months. The mean modified Harris hip scores did not differ significantly between patients with osteopenia and osteoporosis at any time point. Additionally, the type of surgical fixation (intramedullary versus extramedullary) showed no significant impact on functional outcomes. Conclusions: Zoledronic acid administration in elderly hip fracture patients may reduce mortality and enhance functional recovery. The study supports its use in postoperative care to improve outcomes, although larger, randomized controlled studies are needed to confirm these findings. The results suggest that zoledronic acid can be an effective adjunct therapy in managing osteoporosis-related hip fractures in the geriatric population.